1989
DOI: 10.1002/lsm.1900090111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helium‐neon and infrared laser irradiation on wound healing in rabbits

Abstract: We examined the biostimulating effects of helium-neon laser radiation (HeNe; 632.8 nm), pulsed infrared laser radiation (IR; 904 nm), and the two combined on skin wound healing in New Zealand white rabbits. Seventy-two rabbits received either 1) no exposure, 2) 1.65 J/cm2 HeNe, 3) 8.25 J/cm2 pulsed IR, or 4) both HeNe and IR together to one of two dorsal full-thickness skin wounds, daily, for 21 days. Wound areas were measured photographically at periodic intervals. Tissue samples were analyzed for tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
90
0
24

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(127 citation statements)
references
References 14 publications
13
90
0
24
Order By: Relevance
“…22,40,41 Polarized light may reproduce nearly 80% of the effects of the laser, but nonpolarized light may not.42 Polarization has also been suggested as an important factor on tissue responses.26,43 Despite earlier reports suggesting that laser light may inhibit or have no effect on wound healing, meticulous analysis of evidence and problems on the parameters used30,44-48 or consequence of the systemic effect of the laser therapy remain. 49,50 It is important to consider that the use of coherent and incoherent light results in different effects on living tissues and most studies suggested that the use of coherent light achieves better results.13 Considering that semiconductor lasers are coherent and mostly partially polarized, when the laser beam reaches the surface it becomes further polarized due to the formation of laser speckles. The degree of polarization decreases in a direct relationship of the depth of penetration within the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…22,40,41 Polarized light may reproduce nearly 80% of the effects of the laser, but nonpolarized light may not.42 Polarization has also been suggested as an important factor on tissue responses.26,43 Despite earlier reports suggesting that laser light may inhibit or have no effect on wound healing, meticulous analysis of evidence and problems on the parameters used30,44-48 or consequence of the systemic effect of the laser therapy remain. 49,50 It is important to consider that the use of coherent and incoherent light results in different effects on living tissues and most studies suggested that the use of coherent light achieves better results.13 Considering that semiconductor lasers are coherent and mostly partially polarized, when the laser beam reaches the surface it becomes further polarized due to the formation of laser speckles. The degree of polarization decreases in a direct relationship of the depth of penetration within the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some physical methods, including therapeutic ultrasound and laser treatments, were found to accelerate and facilitate wound healing and increase scar quality [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, conflicting findings have been reported in some studies, and some investigators found no treatment effect on accelerating the repair of wounds [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers concluded that some physical methods, including therapeutic ultrasound and laser treatments, accelerate and facilitate wound healing and increase scar quality [4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Braverman et al (1989) comparou a cicatrização de lesões num mesmo animal, sendo que apenas uma ferida foi irradiada com laser.…”
Section: Discussionunclassified